Over There : Living with the U.S. Military Empire from World War Two to the Present - Moon, Seungsook, 1963-; Höhn, Maria, 1955- (Book collections on Project MUSE., 2010)
A collection of essays exploring the world-wide U.S. military base system and its interplay with social relations of gender and sexuality in the U.S. and foreign host nations.